Zinc Acetate as a Cross-Linking Agent in the Development of Enteric Microcapsules for Posaconazole - Marta Szekalska; Giedrė Kasparavičienė; Jurga Bernatonienė; Eliza Wolska; Paweł Misiak; Karolina Halina Markiewicz; Agnieszka Zofia Wilczewska; Anna Czajkowska-Kośnik; Katarzyna Winnicka (Pharmaceutics)
Background/Objectives: Posaconazole is an antifungal agent from triazoles with variable bioavailability. To avoid its irregular absorption caused by gastric conditions and ensure more repeatable pharmacokinetic enabling the maximization of its absorption regardless of food intake without the need to administer multiple doses, can be provided by the technology of enteric drug preparations. The cross-linking of polysaccharide polymers with divalent and trivalent cations enables multi-unit formulations to be obtained that prevent drug absorption in the stomach. Microcapsules, as an example of multi-unit drug dosage forms, provide more predictable gastric emptying, depending on nutritional status, and spread extensively throughout the gastrointestinal tract. Methods: Therefore, the utilization of zinc acetate for the cross-linking of the alginate and pectin mixture was evaluated. The obtained formulations were evaluated for the impact of cross-linking process and pectin’s presence on their pharmaceutical, mucoadhesive, physicochemical and antifungal properties. Results: It was shown that cross-linked microcapsules by zinc acetate provided delayed posaconazole release. Additionally, the cross-linking process with Zn2+ ions significantly enhanced antifungal activity against the analyzed Candida strains. It was observed that pectin content in the formulation enhanced the swelling ability in an intestinal condition and increased the mucoadhesive properties of drug-loaded formulations to the intestinal mucosa.